Correspondencia entre Charles D. Hurrey y Roberto H. Todd - Todd, Roberto H.; Hurrey, Charles D. (My University, 1919)
Carta relacionada a almuerzo en honor de Roberto H. Todd.
Keywords: Hurrey, Charles D.--Correspondence.; Hurrey, Charles D.--Correspondencia.; Todd, Roberto H.--Correspondence.; Coxhead, George; Babcock, George; Manuel, Arthur; Hurrey, C. D.; Hurrey, E. T.; Warren, C. J.; Monroe, Paul; Winton, G. B.; Osuna Brothers